4.13 THE PROBLEM OF SOCIETY AND THE STATE IN THE VIEWS OF EUROPEAN SCIENTISTS - Salimov Bakhriddin Lutfullaevich. Professor at Tashkent State Transport University. BAXSHILLOYEV SANJARBEK SAYFULLO O‘G‘LI. Student at Tashkent State Transport University (Innovative technologies in construction Scientific Journal, 2023)
ANNOTATION The article analyzes Machiavelli’s opinions about society and its social relations, inequality and unrest, as well as the opinions about this problem in European personal society and the fact that many scholars who lived in all periods of the past took this issue seriously and viewed it as an important factor that would maintain the peace of society and ensure its stable development in the future. done Key words: society, equality, privileges, inequality, laws, customs. The law, rules and discipline of society were shaped or shaped on the basis of these religious and moral values. This is not the fault of religion, but as we mentioned above, it is the fault of the clergy who used religion for their own personal interests and misapplied religion to the life of society. Let us dwell on Machiavelli’s remark that “The end justifies the means.” Since this comment was raised, many opinions have been and are being expressed on this matter. There are different opinions about this relationship. Some approve of this idea, others are against it. So what did Machiavelli mean by this statement? At the same time, Machiavelli meant that the head of state must use all means for the development of his country, the peace and well-being of his people, and use all means for the benefit of the entire nation, even if some of these means are immoral, and they are against some representatives of that nation, and also against people of other countries, even if it causes oppression and suffering. Just as a coin has two sides, Machiavelli’s reasoning has both positive and negative sides. The positive side is that the ruler works to ensure the prosperity of his country and the well-being of his people. It is important not to forget that when a country develops, when the head of this country wants this first and foremost and is in constant search. It is also important that the head of state loves his people and his country. After all, a ruler who loves his people and his country always thinks about the future of his country and creating a decent life for his compatriots. In recent days, the slogan “government authorities should be civil servants” has been launched in our country and everyone has been asked to follow it. To create a decent lifestyle for our people, much more is being done that cannot be listed. All this means one thing, it means that we are led by a man who loves his people and his country. This should be done with gratitude. René Descartes, who went down in history with his important scientific research in the fields of mathematics, geometry and physics, is one of the thinkers who left an indelible mark on the development of philosophical thought with his remarkable philosophical views. “Descartes, who was not indifferent to the processes taking place in society, describes several of his moral procedures. On their basis, he builds his life principles, and among them the first rule is obedience to the laws and customs of his country. The development of social relations is determined by the level of education, mental and intellectual potential, spiritual, cultural, political and legal literacy of members of society. The experience of the development of human society has already proven the correctness of this conclusion. This is confirmed by the opinions of many famous thinkers in the field of philosophy. For example, Julien Offrede La Mettrie writes on this subject: “Even if you yourself suffer, spread enlightenment and serve society.” Indeed, education has a great role and importance in social relations. Because. studying and following the laws of social relations is carried out through the dissemination of education. The factors that develop social relations can without hesitation include the principle of science and education. In fact, science is part of enlightenment, an integral part of it. There are also modern trends in philosophy, such as scientism and anti-scientism, that study the role of science in social relations. To make it more understandable to people, the concepts of science and education are often used together. Then the question naturally arises. Well, if following laws and customs is necessary and beneficial, then why shouldn’t everyone follow this procedure. Who are those who violate the laws of the state, who deny the customs of society? The correct answer to this question can be given the following several considerations: Firstly, the laws established in the state are unjust, and the established customs are outdated. Such situations exist in times of slavery, feudalism, dictatorships and autocratic regimes based on individual power; secondly, the presence of different approaches to compliance with laws and customs. For example, what is impossible for many people is possible for others. Or, in other words, there is punishment for some of those who disobey laws and customs, but not for others; thirdly, the laws of the country are fair and morals are in order, but citizens do not obey them for various reasons, sometimes from immorality, sometimes from legal illiteracy, sometimes from negligence, sometimes intentionally and for other reasons. REFERENCES Salimov B.L. Expression of Dialectic Categories in the Individual’s Social Life // eu. International Journal of InnovativeAnalyses and Emerging Technology. Volume: 1, lssue 4, 2021. -Р.16-18. Salimov Baxriddin Lutfullaevich. The philosophical role of dialectical categories in human life. Oriental Renaissance: Innovative, educational, natural and social sciences. Volume: 1, lssue 6, 2021. -Р.406-410. Salimov Baxriddin Lutfullaevich. Prospects of Development of Communication and Transport System in Uzbekistan. WEB OF SYNERGY: International Interdisciplinary Research Journal. Volume 2 Issue 2, Year 2023 ISSN: 2835-3013. Salimov, B., Madalimov, T. (2023). Transport falsafasi. Globe Edit. Salimov Bakhriddin Lutfullaevich. The Importance of Sea Transport in the Communication System. WEB OF SYNERGY: International Interdisciplinary Research Journal. Volume 2 Issue 1, Year 2023 ISSN: 2835-3013. Salimov Bakhriddin Lutfullaevich. The Influence of the Transport and Communication System on Social Relations. Web of Semantic: Universal Journal on Ie Education. Volume 2 Issue 2, Year 2023. ISSN: 2835-3048. Salimov Bakhriddin Lutfullaevich. Reforms in the Fields of Communication and Transport and their Social Impact. Web of Semantic: Universal Journal on Ie Education. Volume 2 Issue 2, Year 2023. ISSN: 2835-3048. Салимов Б.Л. Ижтимоий муносабатларнинг коммуникация ва транспорт тизими билан детерминистик боғлиқлигининг гносеологик таҳлили. Фалсафа фанлари доктори диссертацияси. Ўзбекистон Миллий университети. Тошкент. 2022, 224 б. Salimov Bakhriddin Lutfullaevich, Tursunov, Shokhijakhan Ravshanovich, Haydarov, Mehriddin Nuriddin Ugli (2023). SYNERGETIC APPROACH IN THE ANALYSIS OF SOCIAL RELATIONS. Oriental renaissance: Innovative, educational, natural and social sciences, 3 (3), 1001-1007. Bakhriddin Lutfullaevich Salimov. NEGATIVE CONSEQUENCES OF SCIENCE AND TECHNOLOGY DEVELOPMENT. International Conference" Law, Economics and Tourism sciences in the modern world". 2023/5/1. С. 5-10.